The Concept of Childfree Perspective of Law Number 1 Year 1974 on Marriage and Compilation of Islamic Laws - Vickry Maulanna Sudrajat; Kosim Kosim; Didi Sukardi (UIN Siber Syekh Nurjati Cirebon, 2025)
Modernization in the current era has brought significant changes to various aspects of life, including the institution of Marriage. One emerging phenomenon is childfree, which refers to a couple's decision not to have children, either through natural birth or adoption. In Indonesian society, the presence of children is often seen as a blessing and a sign of trust in God. Still, the decision to live without children poses unique psychological and economic challenges for some individuals. This study aims to examine the principles of legal regulation related to the concept of childfree based on Law Number 1 of 1974 concerning Marriage and the Compilation of Islamic Law. The study uses a qualitative method with a normative-descriptive approach, namely normative legal research that relies on literature studies and juridical analysis of legislation and relevant scientific works. Content analysis was used to interpret the data obtained. The results of the study indicate that although legislation emphasizes the importance of offspring in Marriage, there are no explicit provisions prohibiting couples from choosing to live without children. Legally, the child-free practice does not conflict with the marriage regulations in force in Indonesia. However, this decision remains a controversial issue in a society that strongly upholds family values.